The Effectiveness of the Strategy of the Indonesian Armed Forces’ Habema Operation Command in Preserving Peace in Papua - Faiq Dhiya Ulhaq Mauludi (The Republic of Indonesia Defense University, 2026)
This study examines the effectiveness of the counter-insurgency (COIN) strategy implemented by the Habema Operation Command of the Indonesian Armed Forces to counter the separatist movement of the Free Papua Organization and foster peace and security in Papua. The objective of this study is to assess how the strategy integrates military operations, socio-political engagement, and modern intelligence technology to support welfare development, as mandated by Presidential Instruction No. 9 of 2020. A qualitative case study approach was employed, using primary data from interviews with military personnel and secondary data from credible sources, analyzed through Galula’s COIN theory and Kilcullen’s three-pillar framework. The findings indicate that the Habema Operation Command effectively combines hard power (security operations) and soft power (social programs such as access to clean water and agricultural support) to reduce OPM influence and build community trust. However, challenges such as separatist propaganda and inter-agency coordination persist. The study recommends enhanced coordination, increased socio economic investments, and diplomatic efforts to counter international separatist narratives.